ANALISIS SPIKE ATLET BOLA VOLI PASIR INDONESIA - Vivi Novia Eka Putri (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
Abstract Spike is the main weapon used in volleyball games. The purpose of this research was to determine the contribution of spike movement to ball speed. This research used a descriptive correlational method and purposive sampling technique. Samples of this study were 8 volleyball PPLM Yogyakarta athletes. The instrument used in this study was based on 2-dimensional analysis using kinovea software and radar speed gun to determine the speed of the ball. Data analysis was processed using SPSS software version 23. From the results of data analysis there was a significant contribution between angular velocity leg support at take-off to ball speed with contribution value 0,023 < 0,05, and there was a significant contribution between heigh jump at impact ball to ball speed with a contribution value of 0.031 <0.05. These results can support sports coaches in optimizing athletic performance with adequate technical training and using kinematic cues from opposing volleyball players to anticipate the direction of the spike. Keywords : 2D Kinematic ; Spike ; Beach volleyball